Platelet Phenotype Analysis of COVID-19 Patients Reveals Progressive Changes in the Activation of Integrin αIIbβ3, F13A1, the SARS-CoV-2 Target EIF4A1 and Annexin A5 - Ercan, Huriye; Schrottmaier, Waltraud Cornelia; Pirabe, Anita; Schmuckenschlager, Anna; Pereyra, David; Santol, Jonas; Pawelka, Erich; Traugott, Marianna T.; Schörgenhofer, Christian; Seitz, Tamara; Karolyi, Mario; Yang, Jae-Won; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background: The fatal consequences of an infection with severe acute respiratory syndrome coronavirus 2 are not only caused by severe pneumonia, but also by thrombosis. Platelets are important regulators of thrombosis, but their involvement in the pathogenesis of COVID-19 is largely unknown. The aim of this study was to determine their functional and biochemical profile in patients with COVID-19 in dependence of mortality within five-days after hospitalization. Methods: The COVID-19-related platelet phenotype was examined by analysing their basal activation state via integrin αIIbβ3 activation using flow cytometry and the proteome by unbiased two-dimensional differential in-gel fluorescence electrophoresis. In total we monitored 98 surviving and 12 non-surviving COVID-19 patients over five days of hospital stay and compared them to healthy controls (n = 12). Results: Over the observation period the level of basal αIIbβ3 activation on platelets from non-surviving COVID-19 patients decreased compared to survivors. In line with this finding, proteomic analysis revealed a decrease in the total amount of integrin αIIb (ITGA2B), a subunit of αIIbβ3, in COVID-19 patients compared to healthy controls; the decline was even more pronounced for the non-survivors. Consumption of the fibrin-stabilizing factor coagulation factor XIIIA (F13A1) was higher in platelets from COVID-19 patients and tended to be higher in non-survivors; plasma concentrations of the latter also differed significantly. Depending on COVID-19 disease status and mortality, increased amounts of annexin A5 (ANXA5), eukaryotic initiation factor 4A-I (EIF4A1) and transaldolase (TALDO1) were found in the platelet proteome and also correlated with the nasopharyngeal viral load. Dysregulation of these proteins may play a role for virus replication. ANXA5 has also been identified as an autoantigen of the antiphospholipid syndrome, which is common in COVID-19 patients. Finally, the levels of two different protein disulfide isomerases, P4HB and PDIA6, which support thrombosis, were increased in the platelets of COVID-19 patients. Conclusion: Platelets from COVID-19 patients showed significant changes in the activation phenotype, in the processing of the final coagulation factor F13A1 and the phospholipid-binding protein ANXA5 compared to healthy subjects. Additionally, these results demonstrate specific alterations in platelets during COVID-19, which are significantly linked to fatal outcome.